UHPLC-ESI-MS/MS analyses for quantification of phenolic compounds of Nepeta nuda subsp. Lydiae - Abdulmelik Aras, Ercan Bursal, Mehmet Dogru (Journal of Applied Pharmaceutical Science, 2016)
Phenolic compounds of Nepeta nuda subsp. Lydiae leaves were identified by UHPLC-ESI-MS/MS. To the best of our knowledge, phenolic compounds in N. nuda subsp. Lydiae are reported for the first time. Chlorogenic acid, rosmarinic acid and quinic acid, were found to be the most abundant compound in the methanol extract of N. nuda subsp. Lydiae, among the twenty-seven compounds studied by LC–MS/MS. Also, smaller amounts of kaempferol, p-coumaric acid, tr-caffeic acid, apigenin, luteolin and rhamnetin were identified, quantitatively. In conclusion, leaves of N. nuda subsp. Lydiae have high potential of phenolic contents that mainly attributed with biological activities.
Keywords: Nepeta nuda, phenolic acid, chlorogenic acid, rosmarinic acid, quinic acid.